Multi-domain compact modeling of LEDs: An overview of models and experimental data. Issue 12 (December 2015) - Poppe, András
Abstract: Operating parameters of power LEDs are strongly coupled and are mutually dependent. There have been lots of attempts to provide different kinds of multi-domain LED models with different complexity. This paper gives an overview of recently published models and suggests a practical approach in which the forward current is split into two parts in a straightforward manner. One current component is derived from the LED׳s measured radiant flux directly, the other component is calculated as the difference of the net forward current and the previously mentioned current component associated with light emission. Parameters of the proposed model can be identified from isothermal LED characteristics measured in industry standard LED test setups using textbook techniques. Temperature dependence of the model parameters is discussed in detail; including comparison of different models for the temperature dependence of the saturation current in Shockley׳s diode equation.